Peran Sekolah Dalam Meningkatkan Prestasi Ekstrakurikuler Di SD Negeri 11 Banda Aceh - Nova maulita sari; Intan Safiah; Aida Fitri (Jurnal Ilmiah Mahasiswa Pendidikan Guru Sekolah Dasar, 2022)
EThe purpose of this study was to determine the role of school principals and the role of teachers in sports, scouts, and school health units in improving extracurricular achievement. A qualitative approach is an approach used and descriptive research is the type of research. Principals, teachers in sports, scouts, and UKS (school health units) are the subjects of this research. Interviews and documentation are data collection techniques used. Data analysis techniques were carried out in three ways, namely data reduction, data presentation, and drawing conclusions. Based on the results of research at SD Negeri 11 Banda Aceh, the achievements of extracurricular activities continue to increase every year, the interest and curiosity of children to join extracurricular activities also increases due to the appreciation, motivation and support from the school and the children's parents. From the above problems, it is hoped that parents can still accompany, direct, and also guide children during extracurricular activities so that children continue to participate in extracurricular activities to the maximum.